The effects of China's universal two-child policy - Zeng, Yi; Hesketh, Therese (The Lancet (British edition), 2016)
In October, 2015, China's one-child policy was replaced by a universal two-child policy. The effects of the new policy are inevitably speculative, but predictions can be made based on recent trends. The population increase will be relatively small, peaking at 1·45 billion in 2029 (compared with a peak of 1·4 billion in 2023 if the one-child policy continued). The new policy will allow almost all Chinese people to have their preferred number of children. The benefits of the new policy include: a large reduction in abortions of unapproved pregnancies, virtual elimination of the problem of unregistered children, and a more normal sex ratio. All of these effects should improve health outcomes. Effects of the new policy on the shrinking workforce and rapid population ageing will not be evident for two decades. In the meantime, more sound policy actions are needed to meet the social, health, and care needs of the elderly population.